(untitled) (Human Factors in Design, 2023)
The objective research of evaluating the physical space of the home office used by teachers, based on the domains of specialization of ergonomics and NR-17, justified by the current context of the pandemic that required a series of changes in the performance of their professional activities. Of an applied nature, with a qualitative approach and with exploratory and descriptive objectives, the study was developed in four phases: (1) data collection; (2) development and application of the questionnaire; (3) data analysis and treatment and (4) ergonomic contributions. As a result, it is understood that ergonomics can contribute to the strategic planning of educational institutions, whether in the face-to-face and distance modalities.